2002
DOI: 10.1086/341487
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Treatment ofAcanthamoebaKeratitis

Abstract: Infection of the eye caused by Acanthamoeba species constitutes a burgeoning and unsolved problem. Of individuals with Acanthamoeba keratitis, 85% wear contact lenses; abrasion of the cornea is implicated. Corneal infection often can be prevented by good lens care and hygiene. Severe Acanthamoeba keratitis often can be very difficult to treat; surgery can be less than successful and may lead to further problems. The encysted stage in the life cycle of Acanthamoeba species appears to cause the most problems; ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 72 publications
1
40
0
8
Order By: Relevance
“…Indeed, in a recent study, we found that tears of healthy individuals contain antibodies against Acanthamoeba MBP, and oral immunization with rMBP protects against Acanthamoeba keratitis in a hamster animal model and this protection correlates with the appearance of MBP-specific IgA in tears of immunized animals. 3 The MBP-specific IgA in tears is likely to provide protection by preventing the parasite binding to the corneal epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in a recent study, we found that tears of healthy individuals contain antibodies against Acanthamoeba MBP, and oral immunization with rMBP protects against Acanthamoeba keratitis in a hamster animal model and this protection correlates with the appearance of MBP-specific IgA in tears of immunized animals. 3 The MBP-specific IgA in tears is likely to provide protection by preventing the parasite binding to the corneal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Granulomatous amoebic encephalitis is nearly always fatal because of the lack of an effective treatment. In immunocompetent individuals, Acanthamoebae provoke a debilitating vision-threatening corneal infection known as Acanthamoeba keratitis (AK) 1 (3)(4)(5). AK is characterized by intense pain and a slowly worsening clinical course.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polyhexamethylene biguanide has been demonstrated to be effective, especially if applied in conjunction with other agents. Chlorhexidine applied hourly is also effective, and kills both cysts and trophozoites (20). A successful outcome in patients treated medically is noted in up to 88%, the remainder requiring corneal debridement and possibly penetrating keratoplasty.…”
Section: Case Presentationmentioning
confidence: 99%
“…In the present study, we demonstrate that oral immunization with recombinant MBP ameliorates AK in a hamster animal model and that this protection is associated with the presence of elevated levels of anti-MBP immunoglobulin A in the tear fluid of the immunized animals.Acanthamoeba castellanii keratitis (AK) is a rare but painful and devastating infection of the cornea that is difficult to diagnose and treat (2,4,8,11,13,16). We have recently shown that acanthamoebae express a mannose-binding protein (MBP) that mediates the adhesion of the amoebae to corneal epithelial cells (3,5,6,18) and that anti-MBP immunoglobulin A (IgA) antibodies are present in the human tear fluid of healthy individuals…”
mentioning
confidence: 99%